KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MENINGKATKAN BUDAYA ORGANISASI DI SMA NEGERI 3 BENGKAYANG - Debora, Veronika Narulita; Wahyudi, Wahyudi; Syukri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to find out how the school principal's visionary leadership improves organizational culture in SMA Negeri 3 Bengkayang. Specifically about visionary leadership strategies, innovations by school principals, as well as supporting and inhibiting factors in improving organizational culture.This study uses a qualitative descriptive research method with a case study approach. The research subjects were 4 participants. Principal 1 man aged 47 years; teacher 1 woman aged 36 years; administrative staff 1 woman aged 31 years; student 1 male aged 17 years.Data collection techniques used were interviews, direct observation, and retrieval of several documents using interview guides, observation guides, and documents.The conclusions from this study are 1) the school principal's visionary leadership strategy in improving organizational culture shows good results. 2) innovation by school principals in improving organizational culture by building communication with a family approach, providing motivation and appreciation for each result achieved, giving freedom to innovate and building creativity, etc. 3) the supporting factors for visionary leadership are having a wise attitude, setting an example, respecting each other, and strengthening a sense of kinship. The inhibiting factor is the difference in the character of the members of the organization. There is still ego and selfishness.The implication of the results of this study is that visionary leadership implemented by school principals is successful in improving organizational culture.